2019
DOI: 10.1002/anie.201904671
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Photosensitized Aryl and Alkyl Decarboxylative Functionalization Reactions

Abstract: Despite significant progress in aliphatic decarboxylation, an efficient and general protocol for radical aromatic decarboxylation has lagged far behind. Herein, we describe ag eneral strategy for rapid access to both aryl and alkyl radicals by photosensitized decarboxylation of the corresponding carboxylic acids esters followed by their successive use in divergent carbon-heteroatom and carbon-carbon bond-forming reactions.I dentification of as uitable activator for carboxylic acids is the key to bypass ac ompe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
104
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 201 publications
(111 citation statements)
references
References 65 publications
4
104
0
3
Order By: Relevance
“…Upon exploring the various reaction parameters in line with our previous experience with oxime esters, we found that the oxime ester 1 a provided the desired carboimination product with acrylonitrile ( 2 ) when [Ir(dF(CF 3 )ppy) 2 (dtbbpy)](PF 6 ) ( [Ir‐F] , dF‐(CF 3 )ppy=2‐(2,4‐difluorophenyl)‐5‐trifluoromethylpyridine, dtbbpy=4,4′‐di‐ tert ‐butyl‐2,2′‐bipyridine) was used as the photosensitizer under irradiation with blue LEDs. The desired carboimination product 3 a was afforded in 57 % yield ( 1 H NMR) with complete regioselectivity for the linear C‐radical addition (Table , entry 1).…”
Section: Figurementioning
confidence: 74%
See 4 more Smart Citations
“…Upon exploring the various reaction parameters in line with our previous experience with oxime esters, we found that the oxime ester 1 a provided the desired carboimination product with acrylonitrile ( 2 ) when [Ir(dF(CF 3 )ppy) 2 (dtbbpy)](PF 6 ) ( [Ir‐F] , dF‐(CF 3 )ppy=2‐(2,4‐difluorophenyl)‐5‐trifluoromethylpyridine, dtbbpy=4,4′‐di‐ tert ‐butyl‐2,2′‐bipyridine) was used as the photosensitizer under irradiation with blue LEDs. The desired carboimination product 3 a was afforded in 57 % yield ( 1 H NMR) with complete regioselectivity for the linear C‐radical addition (Table , entry 1).…”
Section: Figurementioning
confidence: 74%
“…Alternatively, oxime esters have also been employed successfully in the photosensitized generation of iminyl radicals through N−O bond homolysis . Recently, we have utilized this distinctive energy transfer (EnT) pathway to develop a general radical decarboxylation process applicable to both aromatic and aliphatic carboxylic acids (Figure B, right) . Nevertheless, all of these approaches are plagued by poor atom economy as either the carboxylate unit or the iminyl unit always become part of the waste stream.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations